A Stand‐Alone Module for Solar‐Driven H2 Production Coupled with Redox‐Mediated Sulfide Remediation. Issue 10 (8th August 2019) - Obata, Keisuke; Shinohara, Yuuki; Tanabe, Shinichi; Waki, Ichitaro; Kotsovos, Konstantinos; Ohkawa, Kazuhiro; Takanabe, Kazuhiro
Abstract : Efficient electrochemical devices are required to convert electric power by intermittent renewable energy sources into a chemical form. The choice of combination in reduction–oxidation reactions can vary depending on the target, which provides different thermodynamics and kinetics. A promising approach for H2 production coupled with sulfide remediation is demonstrated to utilize the intermediate redox media. H2 is produced on the cathode, and soluble redox ions in a reduced form are oxidized on the anode. The ions are then transferred to a separate reactor to oxidize the sulfide ions via a homogeneous reaction, and the reduced redox ions are recirculated. A solar‐driven redox photovoltaic‐electrochemical (PV‐EC) system is operated as a stand‐alone module and is composed of Cu(In, Ga)(S, Se)2 (CIGS) PVs and EC cells in series and operated under natural solar irradiation. A unique EC cell is established in an aqueous‐phase membraneless configuration at ambient temperature, and a cathode is decorated with a semipermeable CrO x ‐based nanomembrane. This allows for selective H2 evolution without causing Fe redox reduction. Remaining issues associated with the stability of the CrO x permselective layer on the cathode are also discussed, which are associated with the formation constant of a soluble metal complex in the presence of ligand counterions. Abstract : A stand‐alone module is designed to demonstrate redox‐mediated H2 S splitting using an ideal redox charge carrier, Fe‐HEDTA, and a nano‐membrane‐coated electrode. A H2 production rate of 222 μmol h −1  cm −2 is recorded under natural light irradiation, which exceeds the value for benchmark water splitting (153 μmol h −1  cm −2 at 10%).